Implementasi Kebijakan Pengembangan Pariwisata Daerah Banten Lama Kota Serang - Arenawati; Titiq Stiawati; Pakhudin (Sawala : Jurnal Administrasi Negara, 2022)
The Banten Lama area of ​​Serang City is a cultural heritage area in the heritage complex of the Sultanate of Banten which consists of various kinds of historical relics which are a separate tourist attraction for tourists. So based on the destination of tourist destinations, the local government carried out the development of Old Banten Tourism and the surrounding environment. This study was conducted to determine and analyze the implementation of tourism development in Banten Lama Serang City as a tourist destination. The theory used is the analysis of Edward III (Nawawi, 2009:138). This research uses a qualitative case study approach with a descriptive method. The data analysis technique used is the Miles & Huberman model. The results of this study indicate that the implementation of the Banten Lama Regional Tourism Development Policy, Serang City is still not optimal and the right implementation to be applied in the Old Banten tourism development is that it requires courage and commitment from the Regional Head in implementing the Banten Lama tourism development policy, regional apparatus organizations ( OPD) in regional tourism development in order to reduce sectoral ego so that coordination and communication run effectively, complete the development of tourism support areas (KPW) so that they can be used for structuring traders and tourist parking centers, synchronization and synergy between tourism institutions in carrying out tourism management policies in Banten Lama with directing tourist visits to tourism support areas and stakeholders must sit together in the plan for the establishment of tourism management institutions in Banten Lama.